ANALISIS KESIAPAN PELAKU EKONOMI SYARI'AH DALAM MENGHADAPI PELAKSANAAN WAJIB AUDIT - Ratno Agriyanto (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
To support the development of Islamic financial institutions the government issued several special regulations related to the control so that the presence of Islamic financial institutions are able to put forward the principle of accountability and professionalism. One of the regulations is the obligation of an audit by a public accounting firm for the institution of Islamic banking. But on the other hand the presence of the Islamic financial institutions has just developed, so it tis possible there is no readiness of the Islamic economic agents to face mandatory execution of audits by public accounting firms. The research objective is to determine how the level of preparedness of Islamic economic actors to the obligations of audits by public accountants and to provide models of affective learning strategies for economic actors, especially the Islamic financial institutions to be ready to implement the provisions of mandatory audit of Islamic Economic institutions.The methodology used in the study are as follows: (1) The subject study of Islamic Economic actors in Semarang with the unit of analysis to managers and accounting clerk (2) data collection method is survey the field to spread questionnaire and interview (3) The analisys used in the study is a qualitative descriptive approach.The results showed that the perpetrators of Islamic Banking in a ready condition for duty audited by a public accountant toward Islamic economic institutions. Although it is generally in ready condition, however there are some disadvantages of competence had by economic actors, such as, lack of understanding of Islamic transactions terms and mechanisms, such as, the terms Sharf, and activity of the bank based in return (profit). To overcome these economic actors expect/hope that there is an Islamic accounting training hoping the ease in obtaining the certification of Islamic accounting.